2015
DOI: 10.1007/s00253-014-6348-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variability of airborne bacterial communities and their correlation with particulate matter chemical composition across two urban areas

Abstract: The study of spatio-temporal variability of airborne bacterial communities has recently gained importance due to the evidence that airborne bacteria are involved in atmospheric processes and can affect human health. In this work, we described the structure of airborne microbial communities in two urban areas (Milan and Venice, Northern Italy) through the sequencing, by the Illumina platform, of libraries containing the V5-V6 hypervariable regions of the 16S rRNA gene and estimated the abundance of airborne bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 39 publications
8
32
0
1
Order By: Relevance
“…As indicated by our conceptual model (Figure 8), our study encompassed multiple processes occurring across a range of days to months that could be expected to impact the aerobiome. In particular, seasonal biotic processes (e.g., vegetation senescence), changes in weather and prevailing winds, and regional-scale human activities (e.g., agriculture) appeared to play roles in the observed shifts in dominant taxonomic groups, as has been noted in other studies (Gandolfi et al, 2015;Lee et al, 2017).…”
Section: Space Is More Important Than Timesupporting
confidence: 73%
“…As indicated by our conceptual model (Figure 8), our study encompassed multiple processes occurring across a range of days to months that could be expected to impact the aerobiome. In particular, seasonal biotic processes (e.g., vegetation senescence), changes in weather and prevailing winds, and regional-scale human activities (e.g., agriculture) appeared to play roles in the observed shifts in dominant taxonomic groups, as has been noted in other studies (Gandolfi et al, 2015;Lee et al, 2017).…”
Section: Space Is More Important Than Timesupporting
confidence: 73%
“…Our rDNA-based bacterial community data is consistent with prior studies and includes several taxonomic orders commonly found in air samples. For example, the Actinomycetales, which were abundant in our samples, are frequently found in the atmosphere ( Brodie et al, 2007 ; Bowers et al, 2013 ; Gandolfi et al, 2015 ) and have been found to be abundant in other studies at high elevation sites ( Bowers et al, 2012 ), including MBO ( Smith et al, 2013 ). There are two reasons to expect this order to be abundant in the atmosphere.…”
Section: Discussionsupporting
confidence: 53%
“…The variability in the prokaryotic cell abundances may be attributed to the distance from nearby shore/land [12], the atmospheric route (i.e., height, duration), the concentration of dust/aerosol, as well as to differences in methodology of aerosol collection and procedure for assessing cell numbers (i.e., microscopy, qPCR, culture-based methods) [12,33,35]. Further, different meteorological conditions such as wind speed, humidity, and atmospheric pH may also affect airborne microbial community structure [36,37].…”
Section: Resultsmentioning
confidence: 99%